Measuring the hydration product proportion in composite cement paste by using quantitative BSE-EDS image analysis: A comparative study. (August 2022) - Li, Lihui; Yang, Jian; Shen, Xiaohan
Highlights: Three BSE image analysis methods based on grey value histogram using for measuring hydration product proportion in cementitious system were compared. Two EDS image analysis methods based on color clustering were proposed and evaluated. The modified BSE-EDS image analysis method achieved best quantification performance and maintained sufficient accuracy and reliability. Abstract: Composite cement has attracted increasing interest in the construction material field from the view of environmental and economic benefits. However, the measurement of hydration product proportion in the composite cementitious system remains challenging due to the heterogeneity of components and the existence of amorphous phases. In this study, three grey value histogram-based Backscattered Electron (BSE) image analysis approaches were compared mutually at first. Then, two color clustering-based Energy Dispersive X-ray Spectroscopy (EDS) image analysis approaches are comparatively developed for intuitively quantifying the hydration product proportion. In the BSE image analysis, results indicate that Overflow Method and Gaussian Mixture Model (GMM) show more reliable and accurate results than Frequency Histogram Method. In the EDS image analysis, GMM is better than K-means in terms of accuracy and reproducibility, and the cluster number of three sufficiently meets the requirement of grain extraction. Finally, the BSE-EDS image analysis, which integrates the merits of above approaches was proposed, achieving the best measurement performance. The hydration product proportions determined by BSE, EDS, and BSE-EDS image analysis approaches in the current research are 73.5%, 74.7%, and 68.1%, respectively. The proposed BSE-EDS image analysis offers a way to identify the hydration products practically, reliably, and visually in the cementitious system.